INVESTIGATION OF COMPREHENSIVE QUALITY INDICATORS ANTIBACTERIAL TEXTILE MATERIALS - ВАРДАНЯН , А.О.; ГАРАНІНА , О.О.; РЕДЬКО , Я.В. (Fashion Industry, 2024)
To investigate the influence of conditions on the effectiveness of dyeing and comprehensive indicators of the quality of textile materials with antibacterial properties based on a mixture of fibers intended for individual protection products of military personnel. Methodology. In the course of the research, the developed technologies for dyeing cotton-polyester textile materials were implemented. A bibliometric analysis of scientific and technical literature was carried out. Determination of indicators of consumer characteristics of developed samples of antibacterial textile materials was performed in accordance with standardized methods of textile materials science. Results. The expediency of using an intensifier in the process of equipping textile materials is substantiated. The results of experimental studies of the specified materials are presented: data from the analysis of complex indicators of the quality of the investigated fabrics, namely hygienic indicators and indicators of resistance to physical and chemical influences. The hygroscopicity, vapor permeability, air permeability, resistance to wet and dry friction, resistance to repeated washing were determined experimentally for each tested sample of the textile material. It is substantiated that for the creation of antibacterial textile materials, the developed materials should combine high hygroscopicity, air and vapor permeability with sufficient moisture absorption. According to the results of research on the hygienic and operational indicators of the developed samples of antibacterial textile materials, a high level of properties was confirmed, which substantiates the expediency of their use for military textile products. Scientific novelty. I ndicators of hygienic and operational properties of developed samples of antibacterial textile materials based on a mixture of polyester and cotton fibers, their compliance with regulatory documents on test methods, which regulate requirements for textile products, were determined. The effect of the intensifier on the efficiency of dyeing, namely intensity of coloring, resistance to washing, dry and wet friction, was studied. Practical value. The use of an intensifier with specified antibacterial properties when dyeing fabrics from a mixture of fibers ensures obtaining samples of dyed textile materials intended for individual protection products of military personnel with high hygienic and operational characteristics.